2019
DOI: 10.3389/fendo.2019.00452
|View full text |Cite
|
Sign up to set email alerts
|

Human Luteinized Granulosa Cells—A Cellular Model for the Human Corpus Luteum

Abstract: In the ovary, the corpus luteum (CL) forms a temporal structure. Luteinized mural granulosa cells (GCs), which stem from the ruptured follicle, are the main cells of the CL. They can be isolated from follicular fluid of woman undergoing in vitro fertilization. In culture, human GCs are viable for several days and produce progesterone, yet eventually steroid production stops and GCs with increasing time in culture undergo changes reminiscent of the ones observed during the demise of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…In the conducted literature comparison, we focused on a few of the most comprehensive proteomic studies of human follicular fluid up to date: Zamah et al, 2015 (742 reported proteins) [ 6 ]; Bianchi et al, 2016 (617 reported proteins) [ 5 ]; Oh et al, 2017 (1079 reported proteins) [ 7 ]; Poulsen et al, 2019 (400 reported proteins) [ 4 ]; Zhang et al, 2019 (1153 reported proteins) [ 9 ]; and Pla et al, 2020 (2461 reported proteins) [ 10 ]. Furthermore, we compared the set of proteins identified in this study to the reported proteomes of biological materials in the proximate physiological environment, i.e., human plasma (Plasma Proteome Database—10,546 reported proteins) [ 21 ]; human oocyte (Virant-Klun et al, 2016—2154 reported proteins) [ 1 ]; and human granulosa cell (Bagnjuk et al, 2019—3642 reported proteins) [ 22 ]. The detailed comparison for each protein is presented in Table S8 and the general overview with cumulative data is presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the conducted literature comparison, we focused on a few of the most comprehensive proteomic studies of human follicular fluid up to date: Zamah et al, 2015 (742 reported proteins) [ 6 ]; Bianchi et al, 2016 (617 reported proteins) [ 5 ]; Oh et al, 2017 (1079 reported proteins) [ 7 ]; Poulsen et al, 2019 (400 reported proteins) [ 4 ]; Zhang et al, 2019 (1153 reported proteins) [ 9 ]; and Pla et al, 2020 (2461 reported proteins) [ 10 ]. Furthermore, we compared the set of proteins identified in this study to the reported proteomes of biological materials in the proximate physiological environment, i.e., human plasma (Plasma Proteome Database—10,546 reported proteins) [ 21 ]; human oocyte (Virant-Klun et al, 2016—2154 reported proteins) [ 1 ]; and human granulosa cell (Bagnjuk et al, 2019—3642 reported proteins) [ 22 ]. The detailed comparison for each protein is presented in Table S8 and the general overview with cumulative data is presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[10]. Furthermore, we compared the set of proteins identified in this study to the reported proteomes of biological materials in the proximate physiological environment, i.e., human plasma (Plasma Proteome Database-10,546 reported proteins) [21]; human oocyte (Virant-Klun et al, 2016-2154 reported proteins) [1]; and human granulosa cell (Bagnjuk et al, 2019-3642 reported proteins) [22]. The detailed comparison for each protein is presented in Table S8 and the general overview with cumulative data is presented in Table 2.…”
Section: The Triple Quad-tof Workflowmentioning
confidence: 99%
“…The research with primary, patient-derived human GCs holds promise for human-focused research, especially because human GCs in vitro are an apt model for the ovulatory follicle and the corpus luteum (Bagnjuk and Mayerhofer 2019). In practical terms, work with human GCs has limitations, particularly with respect to daily availability of comparable cells, given the source (i.e., individual patients) and the rapidly changing phenotype of cultured human GCs.…”
Section: Discussionmentioning
confidence: 99%
“…As GCs fulfill an essential role in the follicle, form the environment for the oocyte and produce steroids, the study of cultured human GCs provides a unique window into the human ovary. A previous study employing a proteomic comparison revealed that IVF-derived human GCs in culture resemble initially luteinizing cells of the ovulatory follicle, but then are more comparable to the large luteinized granulosa cells of the corpus luteum (CL) (Bagnjuk and Mayerhofer 2019). During the culture period, human GCs further undergo striking changes and at later time points they are alike the cells of the regressing CL (Bagnjuk and Sarah Beschta and Katja Eubler are joint first authors.…”
Section: Introductionmentioning
confidence: 99%
“…The follicular aspiration performed during assisted reproductive technology yields granulosa cells as a by-product of the procedure. These granulosa cells are key components of the follicle and, due to their characteristics and function, can provide a unique in vitro model to study the ovary (Bagnjuk and Mayerhofer 2019). However, once in culture they undergo rapid changes, and their heterogeneity arising from their human source makes them a difficult model for matching with specific patient conditions.…”
Section: "Putting the Freeze" On Human Follicular Granulosa Cellsmentioning
confidence: 99%